2020
DOI: 10.3389/fnins.2020.573107
|View full text |Cite
|
Sign up to set email alerts
|

Differences in DNA Methylation Reprogramming Underlie the Sexual Dimorphism of Behavioral Disorder Caused by Prenatal Stress in Rats

Abstract: Prenatal stress (PS) can lead to neuroendocrine and emotional disorders later in adolescence. Sexual dimorphism in these neurodevelopmental outcomes have been observed; however, the underlying mechanisms are not fully understood. To address this issue, we investigated whether there are sex differences in epigenetic reprogramming in rats exposed to PS. Pregnant female rats were subjected to chronic restraint stress from gestational day (G)12 to G18. From postnatal day (P)38 to P45, subgroups of offspring includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…However, most studies explore general epigenetic abnormalities in MDD, lacking the sexual and behavioral specificity. Various rodent models provide powerful tools to ameliorate specific aspects of different depression-like phenotypes ( Catale et al, 2020 ; Chang et al, 2020 ; Lei et al, 2020 ; Kronman et al, 2021 ). For example, social deficits in MDD are easily and superiorly recapitulated in the ELS models with maternal separation and social isolation paradigms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies explore general epigenetic abnormalities in MDD, lacking the sexual and behavioral specificity. Various rodent models provide powerful tools to ameliorate specific aspects of different depression-like phenotypes ( Catale et al, 2020 ; Chang et al, 2020 ; Lei et al, 2020 ; Kronman et al, 2021 ). For example, social deficits in MDD are easily and superiorly recapitulated in the ELS models with maternal separation and social isolation paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that prenatal stress on offspring triggered more display of anxiety-like behaviors in females and more depression-like behaviors in males. These behavioral differences are correlated with sexually different methylation patterns on the promotor region of GR genes, levels of DNA methyltransferases (Dnmt1 and Dnmt3a), and DNA demethylase (Tet methylcytosine dioxygenase 2) ( Lei et al, 2020 ). In general, ELS models recapitulate social deficits induced by early life adversity and are good models to investigate sex differences in epigenetic modifications in MDD.…”
Section: Epigenetic Regulation and Sex Differences In Animal Models Of Major Depressive Disorder Relevant To Social Behaviormentioning
confidence: 99%
“…Lei found that exposure to prenatal stress increased anxiety-like behavior in female offspring, while male offspring exhibited more depressive-like behavior. Sex-specific epigenetic differences were observed, such as the methylation pattern in the promoter region of the GR gene, and changes in the expression of deoxyribonucleic acid (DNA) methyltransferase and DNA demethylase [109].…”
Section: Sex Differences Under the Scope Of The "Unified Model" Of Br...mentioning
confidence: 99%
“…In other words, PS is the stress experienced by pregnant women before giving birth ( 3 ). Exposure to adverse stimuli during pregnancy can cause perpetual negative effects on emotion and cognition, thereby increasing the risk of psychiatric disorders in offspring ( 4 , 5 ). Maternal stress has been described as an important component in the development of offspring's cerebrum, altering the susceptibility to diseases in later life ( 6 ).…”
Section: Introductionmentioning
confidence: 99%